Realizing Post-Disaster Sakinah Families: Analysis of the Resilience of Semeru Eruption Survivors' Families at the Relocation Site from the Maqāṣid al-Sharī’ah Perspective - Rosyadi, Imron; Shofi, Muhammad Aminuddin; Ningsih, Erlin Indaya; Sabri, Fahruddin Ali (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The aim of this research is to analyze the resilience of families of Semeru eruption survivors after being relocated to new housing from a Maqāṣid al-Sharī’ah perspective, referring to the parameters in the Regulation of the Minister of Women's Empowerment and Child Protection, there are four indicators to measure family resilience, namely: physical, economic, social psychological, and socio-cultural. This research includes field studies with a qualitative approach, collecting data using interview techniques, observation and documentation. Content analysis is used as a data analysis technique, with triangulation of data sources as a technique for checking data validity. The research findings show: sequentially the economic aspects felt most affected by the survivors of the Semeru eruption after relocation, loss of assets and difficulty in finding new livelihoods were the causes, in second place the psychological aspect was due to the trauma felt, in third place the socio-cultural aspect was due to having to adapt in a neighborhood with completely new neighbors, and finally the physical aspect due to the lack of health services in the new residence. The efforts made are looking for a new job, strengthening the closeness between family members, strengthening solidarity and solidity between families in a new environment, and strengthening the spiritual aspects of the family. From a Maqāṣid al-Sharī’ah perspective, the condition of survivors' families is not yet ideal, because these families are still classified as vulnerable in terms of economic aspects and the realization of the values of sakinah, mawaddah and rahmah. Referring to the provisions in Law no. 52 of 2009 and Law no. No. 24 of 2007, building the resilience of families of Semeru eruption survivors cannot be placed solely on the family, it needs real support from the government, professionals, academics and civil society, to make this happen.